Mācību izziņas darbības aktivitātes veicināšana 1.klasē matemātikas apguves procesā - Rodionova, Elena (Latvijas Universitāte, 2007)
Šī diplomdarba mērķis ir mācību izziņas darbības aktivitātes veicināšana 1. klasē matemātikas apguves procesā. Pedagoģiskā pētījuma gaitā tika noteikti prioritātes virzieni pirmās klases skolēnu personības veidošanā, kas veicina maksimālo mācību rezultātu sasniegšanu. Diplomdarba autore ir izstrādājusi matemātikas stundu un ārpusstundu nodarbību sistēmu, kas tika atspoguļoti izstrādātajā programmā mācību izziņas aktivitātes veicināšanā 1. klasē. Novadīto nodarbību rezultātā skolēni ir sasnieguši labus rezultātus kā matemātikas jomā, tā arī visā mācību procesa. Diplomdarba autore izstrādāja mācību programmu un metodiskos ieteikumus, ar kuru palīdzību tiek sasniegta skolēnu mācību izziņas aktīva darbība. Atslēgvārdi : aktivitāte, ārpusstundu nodarbības, izziņas darbība, mācību izziņas darbība, mācību stunda.

The aim of the present diploma work is to enhance the level of activity of pupils during the educational-cognitive activity in the process of learning mathematics in the 1st form. In the process of pedagogical research there were established the directions of primary importance in the 1st formers personality formation, which favour the achievement of the best results in education. The author the present diploma work has developed the system of lessons and out-of-school activities in mathematics which are reflected in the presented programme. As a conseguence, with such system the pupils have achieved good results both at math lessons and in the process of education as a whole. The author of the diploma work has developed a content of programme as well as a method, with the help of which the efficiency of pupils in educational-cognitive activity can be achieved. Key words are as follows : cognitive activity, educational-cognitive activity, activity, out of lessons activity, educational lessons.
Promotion of the cognitive activity in the process of acquiring mathematics in Grade 1
Keywords: Pedagoģija